1999
DOI: 10.1002/(sici)1521-4028(199905)39:2<127::aid-jobm127>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a common genotype among strains ofTaylorella equigenitalis isolated from thoroughbred horses in Japan between 1994 and 1996

Abstract: We examined whether or not the genotype J could be detected among 21 new strains of T. equigenitalis isolated between 1994 and 1996 in Japan since our previous report (MiyazawaI et al. 1995). The respective pulsed‐field gel electrophoretic profiles of the 21 Japanese strains, as well as those of an old EQ59 used as a reference strain after separate digestion with the two restriction enzymes, ApaI and NotI, were essentially identical but differed from those of T. equigenitalis NCTC11184T and Kentucky 188, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…These genotypic and phenotypic data, coupled with epidemiological information, confirmed relationships between strains isolated from horses with positive test results within each CEM incident in the United States and also showed a lack of strain relationships between CEM incidents. This study and previous studies (2,8,9,10,11,12,13,16) have demonstrated that PFGE is valuable in discriminating strains of T. equigenitalis. Isolates from horses with positive test results in U.S. outbreaks and isolates from imported horses with positive test results were tested using PFGE, resulting in 15 distinct genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These genotypic and phenotypic data, coupled with epidemiological information, confirmed relationships between strains isolated from horses with positive test results within each CEM incident in the United States and also showed a lack of strain relationships between CEM incidents. This study and previous studies (2,8,9,10,11,12,13,16) have demonstrated that PFGE is valuable in discriminating strains of T. equigenitalis. Isolates from horses with positive test results in U.S. outbreaks and isolates from imported horses with positive test results were tested using PFGE, resulting in 15 distinct genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular genotyping of T. equigenitalis strains by the use of pulsed-field gel electrophoresis (PFGE) or crossed-field gel electrophoresis (CFGE), a variation of PFGE, has been previously performed on isolates from Europe (8), Japan (11,16), Ireland and the United States (12), Norway (13), and Australia (10) by the use of restriction enzymes ApaI and NotI. In Europe, 46 isolates of T. equigenitalis from six countries were classified into 18 genotypes (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…From 1980 to 1996, Matsuda and Miyazawa performed crossed-field gel electrophoresis of restricted genomic DNAs, after separate digestion with ApaI and NotI, against 130 isolates of T. equigenitalis from Thoroughbred mares and stallions in Japan. They reported that only a single genotype was present among all of the isolates [9,10].…”
mentioning
confidence: 99%
“…Since then, although CEM has been eradicated from Thoroughbred populations in the United States, Australia and almost European countries, the disease continues to be a problem among Thoroughbred breeders in Japan, causing considerable economic loss. Despite bacterial isolation testing of all broodmares and stallions in main Thoroughbred breeding areas of Japan every inter-breeding season since 1980, occurrence of CEM has persisted and T. equigenitalis has been isolated every year to date [8,9].…”
mentioning
confidence: 99%